EXPLOITATION OF HETEROSIS AND INBREEDING DEPRESSION FOR YIELD, HYBRID SEED YIELD, NUTRITIONAL AND PROCESSING QUALITY IMPROVEMENT IN TOMATO (Solanum lycopersicum L.) UNDER NORTH INDIAN CONDITIONS - CHANDAN KUMAR; SURENDRA PRASAD SINGH (The Bioscan, 2024)
A diallel analysis was carried out to study the heterotic performance in F1 and F2 generation of tomato for yield, nutritional and processing quality. The study exposed that significant positive as well as negative heterosis and inbreeding depression was recorded in most of the crosses for all the traits under observation. This experiment comprising a total of 64 treatments (28 F1 +28 F2 +8 parents) one standard check (H-86) was evaluated in RBD. Promising combination for average fruit weight and number of seeds per fruit was Arka Meghali x Punjab Chhuhara (19.41% and 75.89%, respectively) showing highest significant heterosis. Pant T-3 x H-24 (60.11%) showed highly significant positive heterosis over better parent for yield per plant along with considerable inbreeding depression while, H-88-78-1 x Azad T-5 (31.30%) cross showed promising results for ascorbic acid content and H-24 x Sel-7 cross shows potential hybrid in respect to average heterosis (16.32%) and heterobeltiosis (16.56%) for TSS. Punjab Chhuhara × H-88-78-1 (40.43%) and Punjab Chhuhara × Arka Alok (36.90%) had showed maximum average heterosis and heterobeltiosis for acidity as ACA trait however Arka Alok x Azad T-5 (32.29%) was hopeful hybrid combination for the trait lycopene content.